Imaging-based assessment of rectus abdominis muscle thickness in an adult population: evaluating possible anthropometric relationships - Egwu, Ogugua Augustine; Ukoha, Ukoha Ukoha; Asomugha, Lasbrey A.; Okorie, Sylvester (Medical Studies/Studia Medyczne, 2014)
Introduction: Very little attention has been paid to muscle architecture in the Sub-Saharan African environment, and the rectus abdominis muscle, being a stabilising agent in the trunk, should not be left out. Considering the incidence of trunk musculoskeletal discomfort, it is necessary to assess the rectus abdominis muscle. Aim of the research: To assess the thickness of the rectus abdominis muscle in an apparently healthy adult population using ultrasound and to evaluate its possible relationship with important anthropometric variables. Material and methods : A total of 120 healthy subjects made up of 60 males and 60 females, who gave their written consent, were recruited for this study. B-mode ultrasound was used to assess the rectus abdominis muscle. Anthropometric variables were also assessed. Results: The results show that the rectus abdominis thickness (RAT) was 14.68 ±2.92 mm and 14.37 ±2.74 mm for the right (RRAT) and left (LRAT) sides, respectively. The males had significantly thicker muscles than the females (p = 0.004) and the RAT correlated positively with age, weight, height, body mass index, body surface area, waist circumference, and conicity index. Conclusions: These results show robust myoanthropometric relationships that will assist surgeons in reconstructive procedures involving the muscle. They will also serve as a guidepost in the biomechanical assessment of the muscle in lifting sports for an African population, in the study of muscle flaps, and in the general evaluation of trunk mass.